Land Use Dynamics and Challenges in Leh District: A Temporal Analysis of Recent Three Decades: RESEARCH PAPER - M. K. Gaur; GOYAL, R.K. (Annals of Arid Zone, 2025)
The cold arid region of Ladakh, India, presents unique challenges to agriculture due to its harsh climate, limited arable land, and increasing pressures from population growth, tourism, and climate change. This study examines land use dynamics, agricultural productivity, and food security in Leh District, analyzing how these factors interact with socioeconomic and environmental changes. Using data from the Ladakh Autonomous Hill Development Council and other regional sources spanning 1985-2019, land use patterns, agricultural practices, and livestock contributions have been assessed and analyzed. Findings indicate that while the area under cultivation remains static, intensification and diversification of farming practices are critical for meeting food demands and enhancing livelihoods. While challenges like soil erosion, water scarcity, and land degradation threaten agricultural productivity, opportunities such as protected cultivation, high-value crops, and renewable energy provide viable pathways to sustainability. Policy recommendations highlight the need for technological innovation, sustainable land management, and value-added processing to strengthen food security and enhance economic resilience in this fragile ecosystem.